The Effects of a Culturally Tailored, Patient-Centered Psychosocial Intervention in South Korean Cancer Survivors. (November 2019) - Kim, Dohun; Chang, Sun Ju; Lee, Hyun Ok; Lee, Seung Hee
This study aimed to develop a culturally tailored, patient-centered psychosocial intervention program and to investigate the effects of the program on health-related quality of life, sleep disturbance, and depression in cancer survivors. This was a one-group pretest and posttest design. A total of 19 cancer survivors participated in the program. The program was designed to have an 8-week duration with one class per week. Every class was composed of a 90-min education session and a 90-min exercise. Among the health-related quality of life subscales, the scores of global health status/quality of life, physical functioning, and emotional functioning at posttest were statistically increased than those at pretest. Fatigue scores significantly decreased, whereas no changes were observed in sleep disturbance or depression scores. The findings of this study suggested that a culturally tailored, patient-centered psychosocial intervention could be applied in clinical settings to improve health-related quality of life in cancer survivors.